Joint strength reduction factor of internally ring-stiffened tubular joints at elevated temperatures. Issue 10 (October 2016) - Lan, Xiaoyi; Wang, Fan; Luo, Zhifeng; Liu, Dingding; Ning, Chen; Xu, Xiaofeng
This article presents the results of a numerical parametric study on the ultimate strength of internally crown- and saddle-stiffened circular hollow section tubular DT-, T-, and Y-joints subjected to brace axial compression or tension at elevated temperatures. Using well-validated finite element models, an extensive study of 640 ring-stiffened tubular joints consisting of 36 DT-joints, 36 T-joints, and 8 Y-joints at different temperatures ranging from 20°C to 800°C was conducted. The strength of the stiffened joints was obtained from finite element analysis. The joint strength reduction was compared with the reduction factors of steel yield stress and elastic modulus at elevated temperatures. The parametric study shows that the effects of joint geometric parameters and stiffening position on the strength reduction of the stiffened DT-, T-, and Y-joints at elevated temperatures fall in a narrow range. An equation for predicting the strength reduction of the stiffened DT-, T-, and Y-joints at elevated temperatures was proposed by introducing a temperature factor. The statistical analysis shows that the proposed equation could provide reasonably accurate joint strength predictions.